2010
DOI: 10.1161/strokeaha.110.592535
|View full text |Cite
|
Sign up to set email alerts
|

Low Rates of Acute Recanalization With Intravenous Recombinant Tissue Plasminogen Activator in Ischemic Stroke

Abstract: Background and Purpose-Acute rates of recanalization after intravenous (IV) recombinant tissue plasminogen activator (rt-PA) in proximal vessel occlusion have been estimated sparingly, typically using transcranial Doppler (TCD). We aimed to study acute recanalization rates of IV rt-PA in CT angiogram-proven proximal (internal carotid artery [ICA], M1 middle cerebral artery [MCA], M2-MCA, and basilar artery) occlusions and their effects on outcome. Materials and Methods-The CT angiogram database of the Calgary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
434
4
21

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 660 publications
(483 citation statements)
references
References 23 publications
11
434
4
21
Order By: Relevance
“…3,4 The major reason for the limited efficacy of alteplase is the modest rate of early reperfusion among patients with a large-vessel occlusion. 5,6 Local treatment of large-vessel occlusion began with intraarterial delivery of thrombolytic drugs. 7 The Prolyse in Acute Cerebral Thromboembolism (PROACT) II study was the first positive trial of endovascular treatment involving patients with angiographically visualized occlusion of the middle cerebral artery.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 The major reason for the limited efficacy of alteplase is the modest rate of early reperfusion among patients with a large-vessel occlusion. 5,6 Local treatment of large-vessel occlusion began with intraarterial delivery of thrombolytic drugs. 7 The Prolyse in Acute Cerebral Thromboembolism (PROACT) II study was the first positive trial of endovascular treatment involving patients with angiographically visualized occlusion of the middle cerebral artery.…”
Section: Resultsmentioning
confidence: 99%
“…Workflow times were measured against predetermined targets. The primary outcome was the score on the modified Rankin scale (range, 0 [no symptoms] to 6 [death]) at 90 days. A proportional odds model was used to calculate the common odds ratio as a measure of the likelihood that the intervention would lead to lower scores on the modified Rankin scale than would control care (shift analysis).…”
Section: Methodsmentioning
confidence: 99%
“…10) Previous studies have shown a recanalization rate after intravenous rt-PA therapy of only 4.4%-12.5% for ICO 11,12) but 51.7% for MCO. 13) To improve the recanalization rate, intra-arterial thrombolytic therapy 5,11,14) and surgical thrombectomy 15) have been performed, but there has been no report that these methods markedly improved the prognosis of ICO, particularly T-occlusion.…”
Section: Discussionmentioning
confidence: 98%
“…1 Data from the 1287 patients (634 assigned to endovascular thrombectomy, 653 assigned to standard care) allowed more precise estimates of overall treatment effect (adjusted common odds ratio for reduced disability 2·49, 95% CI 1·76-3·53; p<0·0001and absence of heterogeneity strengthened conclusions about the consistency of effects across major subgroups of age and severity. The number needed to treat with endovascular thrombectomy to reduce disability by at least one level on the modified Rankin Scale (mRS) for one patient was 2·6, which is extraordinary in itself and a huge advance in care for patients with stroke caused by occlusion of the major intracranial carotidterritory vessels, who often respond poorly to optimal medical care with intravenous thrombolytic drugs 2 and have high risk of mortality or disability. Updates to European and North American guidelines [3][4][5] for acute stroke management have already reflected the findings of these trials by recommending endovascular thrombectomy in suitable patients, conclusions supported by the HERMES analysis.…”
Section: Hermes: Messenger For Stroke Interventional Treatmentmentioning
confidence: 99%